Vaksin Terapeutik yang Menargetkan Onkoprotein E6 dan E7 pada Kanker Serviks - Maya Savira (Fakultas Kedokteran Universitas Riau, 2023)
Cervical cancer is caused by persistent high-risk type of human papillomavirus (HPV) infection. especially types 16 and 18. The choice of cervical cancer therapy is associated with many side effects, tumor drug resistance, and high costs. A more efficient, safe and effective cervical cancer therapy is needed, such as therapeutic vaccine which targets host factors related to E6 and E7 of HPV oncoprotein. The oncoprotein E6 targets and inhibits p53, whereas E7 inhibits pRb. Therapeutic vaccines can be used to treat cervical cancer in all stage. Currently, this therapeutic vaccine is under investigation in phase I/II/III clinical trials.